Exploring Factors Surrounding Students’ Entrepreneurial Intentions in Medical Informatics: The Theory of Planning Behavior Perspective - Wu, Wen-Hsiung; Wei, Chun-Wang; Yu, Min-Chun; Kao, Hao-Yun (Frontiers in Psychology, 2020)
The implementation of entrepreneurship and innovation within the health informatics scientific community is relatively sluggish when compared to other disciplines such as computer science and engineering. The purpose of this paper is to explore the cognitive processes involved in developing intentions to enact entrepreneurial behaviors via exploring entrepreneurial awareness as a significant influence on an individual’s intentions to recognize and exploit market opportunities. In this conceptual paper, insights from Ajzen’s Theory of Planning Behavior (TPB) coupled with self-efficacy beliefs are utilized to develop hypotheses from our research questions. TPB has often been applied to entrepreneurial studies, but for the voluminous body of research devoted to intentions, little has delved into the cognitive processes whereby people develop intentions to entrepreneurial behaviors. Thus, our extended framework can better understand the factors behind entrepreneurial intentions. This research used a structured questionnaire as a survey instrument to determine students’ perceptions of entrepreneurial behavior. The questionnaire was completed by a number of students drawn from the different types’ universities in Taiwan. This method allowed respondents to clarify and pose questions. Of the 154 web questionnaires distributed till end of June, 120 were returned, constituting a response rate of 77.9% and Common Method Variance (CMV) had checked. Our results suggest that measuring self-efficacy beliefs in tandem with attitudes toward entrepreneurship provides a better analytical model based on the TPB. The R-Square is 41.2% for full model. Moreover, the results help understand entrepreneurial intentions specifically applied to the medical informatics field which has been under researched. Finally, this study also can guide educators in their efforts to reinforce entrepreneurial behaviors in entrepreneurship education, for example, awareness creation or attractiveness.